Formation and dynamics of attitudes towards refugees in Bulgaria - Mantarova, Anna I. (Sociološki pregled, 2021)
The wave of refugees to Europe after 2011 brought tens of thousands of immigrants to Bulgaria, and the society faced unexpected challenges. The aim of the present study is to establish what the attitudes of Bulgarians to refugees are like, what influences these attitudes, whether and how they change over time. The study is based on information collected in surveys in 2017 and 2019 and survey in areas with refugee accommodation centres. New in the article is that it not only reveals the attitudes and identifies their dependencies, but also traces the dynamics over time. The conclusion is that over time the sense of threat subsides and in the formation of the attitude to refugees more and more importance is given to social qualities, and not so much to religious, racial and ethnic affiliation.
Keywords: refugees; attitudes towards refugees; discrimination; value systems